2014
DOI: 10.2169/internalmedicine.53.1342
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Malignancies in Patients with IgG4-related Disease

Abstract: Objective It has been discussed whether IgG4-related disease (IgG4-RD), including autoimmune pancreatitis (AIP), is associated with malignancy; however, the issue has not been clarified. Methods We analyzed 113 patients with IgG4-RD in whom malignancy was not diagnosed at the time of IgG4-RD onset and the follow-up period was longer than six months. A total of 95 patients had AIP. The mean follow-up period was 73 months. The incidence of the observed malignancies was compared with the expected incidence in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 158 publications
(144 citation statements)
references
References 22 publications
4
132
1
7
Order By: Relevance
“…On the other hand, we previously concluded that IgG4-RD was not associated with an increased incidence of total malignancy [14]. In our experience of 126 patients with IgG4-RD, there were 23 malignancies among 21 patients, which might not be a small figure.…”
Section: Aip Igg4-rd and Total Malignanciesmentioning
confidence: 50%
See 3 more Smart Citations
“…On the other hand, we previously concluded that IgG4-RD was not associated with an increased incidence of total malignancy [14]. In our experience of 126 patients with IgG4-RD, there were 23 malignancies among 21 patients, which might not be a small figure.…”
Section: Aip Igg4-rd and Total Malignanciesmentioning
confidence: 50%
“…As for IPMN, pancreatic cancer was discovered in 2.6 % (17/642) during an average follow-up of 4.8 years in one study [13]. If 100 patients with AIP are necessary to identify one case of pancreatic cancer and the SIR is 3.6, as per our previous report [14], a sample of approximately 450 patients is necessary to demonstrate statistical significance [15]. It is possible that the SIR is much \ 3.6 [16].…”
Section: Aip and Pancreatobiliary Cancermentioning
confidence: 70%
See 2 more Smart Citations
“…Patients with IgG4-RD were reported to be at risk of malignant disease [2]. However some researchers found that the incidence of total malignancies in IgG4-RD patients was similar to that in the general population [9]. One thing is sure that IgG4-RD should be differentiated from malignant diseases.…”
Section: Discussionmentioning
confidence: 99%